Penerapan Metode SMART Dalam Sistem Pendukung Keputusan Rekomendasi Benih Tomat - Fahlevi, Muhammad Reza; Putri, Dini Ridha Dwiki; Indriani, Ulfah; Putri, Fetty Ade; Nasution, Farhan Sya’bandi (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2024)
The spread of tomatoes in Indonesia began from the Philippines and other Asian countries in the 18th century. Initially, the tomatoes first cultivated by the Inca and Aztec tribes were small-fruited and had low productivity. This is clearly different from the current conditions. Tomatoes produced now can weigh up to 0.4 kg each fruit or 8 kg each plant. In addition to their high quality and yield, tomato plants can also adapt to various agro-climatic conditions, from lowland, midland, to highland areas. There are even seeds that are resistant to certain pests and diseases. This research aims to develop a Decision Support System (DSS) using the SMART (Simple Multi Attribute Rating Technique) method to provide recommendations for tomato seeds. The SMART method allows the evaluation of seed alternatives based on various relevant criteria. The research results show that the SMART method is effective in helping farmers choose seeds that suit their specific conditions, improving agricultural efficiency and yields. The recommendation of good tomato seeds is based on five criteria: land recommendation, harvest age, yield potential, weight potential, and disease resistance. System testing results show that the recommended good and quality tomato seed is Gandhi F1, with an accuracy rate of 81.7%.